2017
DOI: 10.4238/gmr16039067
|View full text |Cite
|
Sign up to set email alerts
|

Research Article miR-367 promotes uveal melanoma cell proliferation and migration by regulating PTEN.

Abstract: ABSTRACT. We aimed to investigate the biological role of miR-367 in uveal melanoma cell growth and migration, and the underlying mechanism responsible. Quantitative real-time polymerase chain reaction was performed to evaluate miR-367 expression in uveal melanoma tissue samples and cell lines. A miR-367 mimic, miR-367 inhibitor, and negative control oligonucleotide were transfected into these cells to investigate the function of this microRNA. In addition, the role of PTEN in miR-367-mediated uveal melanoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
21
0
2
Order By: Relevance
“…Other oncogenic miRNAs include miR-155 [85], miR-20a [86], and miR-216a-5p that targets the hexokinase 2 (HK 2 ) gene involved in cell metabolism [87]. Interestingly, two oncogenic miRNAs have been shown to target PTEN in UM, namely miR-454 [88] and miR-367 [89]. Both miRNAs were upregulated in UM cell lines and samples, and had significant effects on promoting cell proliferation, cell cycle, migration and invasion by directly targeting PTEN.…”
Section: Mirna As Oncogenes In Ummentioning
confidence: 99%
See 1 more Smart Citation
“…Other oncogenic miRNAs include miR-155 [85], miR-20a [86], and miR-216a-5p that targets the hexokinase 2 (HK 2 ) gene involved in cell metabolism [87]. Interestingly, two oncogenic miRNAs have been shown to target PTEN in UM, namely miR-454 [88] and miR-367 [89]. Both miRNAs were upregulated in UM cell lines and samples, and had significant effects on promoting cell proliferation, cell cycle, migration and invasion by directly targeting PTEN.…”
Section: Mirna As Oncogenes In Ummentioning
confidence: 99%
“…Both miRNAs were upregulated in UM cell lines and samples, and had significant effects on promoting cell proliferation, cell cycle, migration and invasion by directly targeting PTEN. Individually, miR-454 has been reported to be involved in hepatic stellate cell activation [90], while both miRNAs are involved in TGFβ signalling pathways via the SMAD family of genes [89,91]. These studies highlight that multiple miRNAs are able to target a single gene, and also that data from "single gene-single target" studies must be viewed in a wider context when trying to determine the overall miRNA landscape of UM.…”
Section: Mirna As Oncogenes In Ummentioning
confidence: 99%
“…PTEN immunoreactivity is either lost or weak in 59% of UM, and although PTEN mutations are not common, loss of heterozygosity of at least one PTEN marker was evident in 29 of 38 (76%) tumors, suggesting submicroscopic deletions within the PTEN gene (Abdel‐Rahman et al., ). PTEN expression is also downregulated in UM by overexpression of the microRNAs miR‐367 and miR‐454 (Ling, Lu, Zhang, Jiang, & Zhang, ; Sun et al., ). Importantly, loss of cytoplasmic PTEN expression is associated with shortened disease‐free survival in UM (Abdel‐Rahman et al., ).…”
Section: Oncogenic Signalingmentioning
confidence: 99%
“…Recently, Serocki et al (148) confirmed the role of miR-17 family miRNAs in controlling HIF expression under conditions of hypoxia. Some miRNAs also reduce the expression of phosphatase and tensin homolog (PTEN), promoting PI3K/AKt/mTOR pathway activation (149,150). In addition, Liu et al (151) described the role of miR-216a-5p as an indicator of a better prognosis due to its inhibitory effect on hexokinase 2, an enzyme overexpressed in a wide array of tumours that is directly related to induction of the Warburg effect.…”
Section: Role Of Epigenetics In the Development Of Uveal Melanomamentioning
confidence: 99%